A gene expression atlas of Nicotiana tabacum across various tissues at transcript resolution - Shizhou Yu; Jufen Wan; Jufen Wan; Tenghang Xu; Tenghang Xu; Jie Zhang; Linggai Cao; Jie Liu; Hongfeng Liu; Xueliang Ren; Zhixiao Yang (Frontiers in Plant Science)
Alternative splicing (AS) expands the transcriptome diversity by selectively splicing exons and introns from pre-mRNAs to generate different protein isoforms. This mechanism is widespread in eukaryotes and plays a crucial role in development, environmental adaptation, and stress resistance. In this study, we collected 599 tobacco RNA-seq datasets from 35 projects. 207,689 transcripts were identified in this study, of which 35,519 were annotated in the reference genome, while 172,170 transcripts were newly annotated. Additionally, tissue-specific analysis revealed 4,585 transcripts that were uniquely expressed in different tissues, highlighting the complexity and specialization of tobacco gene expression. The analysis of AS events (ASEs) across different tissues showed significant variability in the expression levels of ASE-derived transcripts, with some of these transcripts being associated with stress resistance, such as the geranyl diphosphate synthase (GGPPS). Moreover, we identified 21,763 splicing quantitative trait locus (sQTLs), which were enriched in genes involved in biological processes such as histone acetylation. Furthermore, sQTLs involved genes related to plant hormone signal transduction, terpenoid backbone biosynthesis, and other resistance pathways. These findings not only reveal the diversity of gene expression in tobacco but also provide new insights and strategies for improving tobacco quality and resistance.